The Differential Expressions and Associations of Intracellular and Extracellular GRP78/Bip with Disease Activity and Progression in Rheumatoid Arthritis - Guoyin Liu; Jianping Wu; Yongqiang Wang; Yuansheng Xu; Chun Xu; Guilin Fang; Xin Li; Jianmin Chen (Bioengineering)
GRP78/BiP, a stress-induced protein and autoantigen in rheumatoid arthritis (RA), exhibits different expressions in various biological fluids and tissues, including blood, synovial fluid (SF), and synovium, all of which are pertinent to the disease activity and progression of RA; however, there is a scarcity of data linking both intracellular and extracellular GRP78/Bip to disease activity and progression of RA. This study was undertaken to investigate the differential expression of GRP78/Bip in blood, SF, and synovium, and to determine their association with disease activity and progression of RA. Patients with RA, osteoarthritis (OA), and traumatic meniscal injury (TMI) without radiographic OA were consecutively recruited for the study. Among patients with RA, six different subgroups were established based on their disease activity and progression. Disease activity was measured using the DAS28 (Disease activity scores in 28 joints) criterion, while disease progression was evaluated using the Steinbrocker classification grade. The levels of GRP78/Bip, TNF-α, and IL-10 were significantly elevated in the serum, SF, and synovium of patients with RA when compared to both the control (CON, TMI Patients) and the inflammation control (iCON, OA Patients) groups (p < 0.05). In terms of disease activity status, as opposed to remission status in RA, the levels of GRP78/Bip, TNF-α, and IL-10 were all elevated in serum and synovium (p < 0.05). However, GRP78/Bip and IL-10 levels were found to be reduced in SF, while TNF-α levels remained elevated. With respect to disease progression in RA, GRP78/Bip levels exhibited a positive correlation with both the stage of RA and the levels of TNF-α and IL-10 in serum and synovium. Nonetheless, a negative correlation was observed between GRP78/Bip levels and the stage of RA in SF, while positive correlations with the levels of TNF-α and IL-10 persisted. The differential expression of GRP78/Bip in blood, SF, and synovium indicated that the potential role and function of GRP78/Bip might vary depending on its specific location within these biological fluids and tissues. The presence of intracellular and extracellular GRP78/Bip was associated with disease activity and progression of RA, suggesting the involvement of GRP78/Bip in the pathogenesis and development of this debilitating autoimmune disorder, as well as its potential as a biomarker for monitoring disease activity and progression of RA.